Genetic polymorphisms and related risk factors of ischemic stroke in a Mongolian population in China - Q. Wu; H. Wu; Yu. L. Orlov; G. Gegentana; W. Huo; A. O. Bragin; N. Wu; S. Suyalatu; F. Zhao; J. Zhao; L. E. Tabikhanova; M. Chen; et al. (Вавиловский журнал генетики и селекции)
Ischemic stroke is caused by an interruption in the flow of blood to the brain and a risk factor for death and disability. Recent genome-wide association studies have identified more than 40 common sequence variants associated with ischemic stroke. However, the results are not always the same in populations with different genetic backgrounds. In the present study, we evaluated a hypothesis that a North Asian population living in a geographic area with unusually harsh environmental conditions would develop unique genetic risks. We investigated the candidate genes for ischemic stroke and risk factors in a Chinese Mongolian population which has not been explored previously. A total of 167 stroke cases and 176 controls were included in the study. Genotyping was performed by amplicon sequencing. The association was detected with single nucleotide polymorphisms (SNPs) located within genes NINJ2 (rs12425791) and ALDH2 (rs2238151) as well as intergenic rs9536591 were significantly associated with ischemic stroke, of which SNP rs12425791 of the NINJ2 gene was the strongest association. ALDH2 gene encodes mitochondrial aldehyde dehydrogenase, involved in the oxidative pathway of alcohol metabolism. Sex, age, body mass index and high blood pressure might be the risk factors. The current work also demonstrated genetic heterogeneity exists between Chinese and other populations. Our study provided the new insights into the genetic basis and environmental factors of ischemic stroke in Mongolian population.